2015
DOI: 10.5301/hipint.5000272
|View full text |Cite
|
Sign up to set email alerts
|

Management of Femoral Bone Loss in Revision Total Hip Arthroplasty

Abstract: Femoral bone loss is frequently encountered during revision total hip arthroplasty. The quality and quantity of remaining bone helps determine the best method for reconstruction. Extensively porous-coated cylindrical stems or titanium fluted tapered devices that achieve fixation in the diaphysis have both demonstrated excellent long-term survivorship. Titanium fluted tapered stems with a modular proximal body allow for more accurate leg length, offset, and version adjustments independent of the distal stem whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…We believed that the nonmodular design would show results comparable to published results with modular stems [23,28,30,31,33]. Several studies [6,14,20] support this view, however some of the medium-to long-term studies [6,14] reflect use of early designs of this prosthesis.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We believed that the nonmodular design would show results comparable to published results with modular stems [23,28,30,31,33]. Several studies [6,14,20] support this view, however some of the medium-to long-term studies [6,14] reflect use of early designs of this prosthesis.…”
Section: Introductionmentioning
confidence: 66%
“…Obtaining fixation in patients with large defects (Paprosky Types IIIB and IV) can be difficult with this design [17]. Numerous authors have reported encouraging clinical and radiologic outcomes with the use of tapered fluted modular titanium stems [22,23,26,30,31,38,39], however, observation of junctional fractures at the modular stems [26] led to increased interest in the use of the nonmodular Wagner SL tapered fluted titanium stem at our institution. We therefore asked: (1) Do repeat revision rates with the Wagner SL stem match published results for this and other implants?…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In this challenging scenario, modular stems are a popular and attractive choice since implant version, offset, and leg length can be handled independently of each other, thus having the potential to better restore hip biomechanics and make the surgical procedure easier. 18,19 The aims of this study were to determine the shortto mid-term clinical and radiographic outcomes and the survivorship of a modular fluted tapered stem in revision THA.…”
Section: Introductionmentioning
confidence: 99%
“…Guidance and treatment options for revision THA are often based on pre-planning using the Paprosky femoral bone loss classification. [13][14][15][16][17] This classification grades bone loss into four types, with Type III having two subsections. A Type I femoral defect is defined as having minimal metaphyseal cancellous bone loss and an intact diaphysis.…”
mentioning
confidence: 99%
“…This is especially the case for the more severe Type III femoral bone defects commonly seen in revision THA. [13][14][15]17 If more than 4 cm of intact diaphyseal bone is available (Type III-A), porous coated cylindrical stems have been recommended for fixation. If less than 4 cm is available (Type III-B), tapered stems are recommended.…”
mentioning
confidence: 99%